Case file tracking system for Badrul Lee & Associates - Lee, Jun Hwa (2010)
Locating items in a huge collection is becoming more and more difficult and time consuming. This appears to be a problem especially in time essential environments such as business environments. With current technology this problem can be solved. RFID is a blooming technology with many different applications. It is currently mostly used in stock management and theft control systems as seen in libraries and shopping complexes. There are also applications of RFID in item tracking but not on a commercial scale and it is done with static objects. However, there lies a possibility of RFID tracking moving objects in real-time. Technology is advancing day by day and it is exists to assist people to live in comfort.